Predicting the Mesiodistal Crown Dimensions of the Permanent First Molars from the Deciduous Second Molars - Al-Dulaimy, Dunia Ahmed (ScientificWorldJournal, 2021)
BACKGROUND: This study aims to formulate regression equations that predict the mesiodistal crown widths of the permanent first molars utilizing the mesiodistal crown widths of the deciduous second molars. METHODS: Fifty pairs of study models belonging to 50 Iraqi children aged eight to nine years with sound mixed dentition were used to measure the mesiodistal crown widths of the permanent first molars and deciduous second molars using a pointed digital sliding caliper with 0.01 mm sensitivity. Side and gender differences were assessed, and the correlations between these teeth were obtained to develop the regression equations. RESULTS: The results revealed no significant side differences, so the samples were merged and analyzed for gender differences, which were found to be significant in all examined teeth except the mandibular permanent first molar. Direct, moderate, and highly significant correlations between the mesiodistal crown widths of the permanent first molars and deciduous second molars were found, which led to the development of regression equations. After applying these equations, the resultant predicted widths were compared to the actual widths, and the results revealed nonsignificant method differences. CONCLUSIONS: A new method was developed to predict the widths of permanent first molars from the adjacent primary second molars with high precision.